STUDY OF GROUND FAULT PROTECTION SYSTEM IN THE MEDIUM VOLTAGE PANEL OF THE MAIN POWERHOUSE AT THE AIRPORT - Muhammad Zaky Isdy; Tamal Basak; Fadhilla Nina (Journal of Airport Engineering Technology (JAET), 2023)
The protection system is a system for securing electrical equipment caused by abnormal conditions such as short circuits (phase contact with the ground), human error, and others and detecting disturbances that occur and overcoming these disturbances in a short time. The ground fault protection system has not been activated at Juanda Airport Surabaya. This research aims to avoid problems that cause ground faults that spread throughout the MV. The Medium Voltage (MV) panel ground fault protection system used by the Main Power House (MPH), namely MPH M-03, for voltage distribution to Air Field Lighting (AFL) substation Airport Operation Building (AOB) substation, and Pump House 4 (PH 4) has not been activated. This study assesses the impact of activating the ground fault protection system for the MV MPH M-03 panel using the SEPAM protection relay. The research method is an exploratory study of the ground fault protection system in the M-03 main powerhouse medium voltage panel. The results showed that using a ground fault protection system for the MV MPH M-03 panel using the SEPAM protection relay is safer due to the ground fault indicator on the equipment. The Ground Fault panel helps protect electrical equipment and supplies from damage caused by ground faults. Quickly shutting off power in the event of a fault prevents excessive current flow that can damage or destroy sensitive equipment. This benefit is significant in industrial environments or areas with valuable equipment where downtime and repairs can be costly. The conclusion is that these systems should be used for safety in voltage transmission and distribution operations. Activating the ground fault protection system, operational safety at Juanda Airport Surabaya will be guaranteed, and it will be safer for the MV panel equipment and safety for the technicians working.